Estimating the prevalence of COPD in an African country: evidence from southern Nigeria - Boni M. Ale; Obianuju B. Ozoh; Muktar A. Gadanya; Yiyang Li; Michael O. Harhay; Akindele O. Adebiyi; Davies Adeloye (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Though several environmental and demographic factors would suggest a high burden of chronic obstructive pulmonary disease (COPD) in many African countries, there is insufficient country-level synthesis to guide public health policy. # Methods A systematic search of MEDLINE, EMBASE, Global Health and African Journals Online identified studies reporting the prevalence of COPD in Nigeria. We provided a detailed synthesis of study characteristics, and overall median and interquartile range (IQR) of COPD prevalence in Nigeria by case definitions (spirometry or non-spirometry). # Results Of 187 potential studies, eight studies (6 spirometry and 2 non-spirometry) including 4,234 Nigerians met the criteria. From spirometry assessment, which is relatively internally consistent, the median prevalence of COPD in Nigeria was 9.2% (interquartile range, IQR: 7.6-10.0), compared to a lower prevalence (5.1%, IQR: 2.2-15.4) from studies based on British Medical Research Council (BMRC) criteria or doctor's diagnosis. The median prevalence of COPD was almost the same among rural (9.5%, IQR: 7.6-10.3) and urban dwellers (9.0%, IQR: 5.3-9.3) from spirometry studies. # Conclusions A limited number of studies on COPD introduces imprecision in prevalence estimates and presents concerns on the level of response available across different parts of Nigeria, and indeed across many countries in sub-Saharan Africa.